Rust. Death of the rocket boy - Lepp, Royden, 1980- (Archaia, 2014)
Jet searches for his place in the Taylor family, while shades of his past return to call him home and convince him that he will never belong. Oz Taylor may know Jet Jones' secret, but convincing the rest of his family may be harder than he counted on. As Oz plots to rid the Taylor farm of the rocket boy, Jet tries to prove himself to the family that has taken him in, in hopes of finding the home he has searched for so long. However, when shadows of Jet's past start coming back into his life, he realizes his days of running may be numbered and he'll have to choose between protecting the Taylors and finding the family he's always wanted.